Tranexamic Acid Associated With Less Wound Complications in Ankle and Hindfoot Surgery: Level III, Retrospective Cohort Study. Issue 16 (15th August 2022) - Moore, Andrew D.; Smith, Benjamin R.; O'Leary, Ryan J.; Hoch, Caroline P.; Gross, Christopher E.; Scott, Daniel J.
Abstract : Introduction: The purpose of this study was to determine whether total ankle arthroplasty (TAA) and ankle/hindfoot fusion patients receiving tranexamic acid (TXA) exhibit fewer wound complications. Methods: A retrospective review was conducted of 212 patients (217 feet) undergoing TAA (n = 72), ankle (n = 36), tibiotalocalcaneal (n = 20), pantalar (n = 1), or hindfoot fusion (ie, subtalar = 47, double = 33, and triple = 8) between 2015 and 2020 by a fellowship-trained foot and ankle surgeon at an academic medical center. Demographics, medical history, complications, and union status were compared between TXA (n = 101) and non-TXA (n = 116) cohorts. The mean follow-up was 1.24 years (range, 0.25 to 4.68). Results: The TXA group had significantly less postoperative infections (5.9% versus 15.5%, P = 0.025). Within a subgroup analysis of ankle/hindfoot fusions, the TXA group exhibited significantly more Charcot neuroarthropathy (20.7% versus 5.7%, P = 0.006) and shorter follow-up duration (0.96 versus 1.30 years, P = 0.030); however, TXA was associated with shorter time to fusion (146 versus 202 days, P = 0.049) and fewer revision surgeries (8.6% versus 21.8%, P = 0.036). Subgroup analysis excluding feet with Charcot also demonstrated less postoperative infections (4.5% versus 14.4%, P = 0.020). Subgroup analysis of TAAs showed fewer cases of superficial infections (2.3% versus 27.6%, P = 0.002) and delayed wound healing (25.6% versus 48.3%, P = 0.047) in the TXA cohort. Discussion: TXA use in ankle/hindfoot surgery was correlated with a reduction in superficial infections and radiographic time to union. The use of TXA in TAA correlated with fewer superficial infections and cases of delayed wound healing. Thus, in addition to other areas of orthopaedics, TXA seems to be beneficial in hindfoot and ankle surgery. Data availability and trial registration numbers: All data were obtained from our institution's medical records. This study is not associated with a clinical trial.